Timing of Adverse Events Following Open Reduction and Internal Fixation of the Ankle. Issue 3 (14th September 2018) - Bohl, Daniel; Lee, Simon; Hamid, Kamran; Lin, Johnny; Holmes, George
Category: Ankle Introduction/Purpose: There is increasing interest in the early identification and treatment of adverse medical events following orthopaedic procedures. The purpose of this study is to characterize the timing of adverse events following open reduction and internal fixation of closed fractures of the ankle. Methods: A retrospective cohort study was conducted using the American College of Surgeons National Surgical Quality Improvement Program. A total of 17, 318 patients undergoing open reduction and internal fixation of closed ankle fractures were identified. For each of eight different adverse events, the median postoperative day of diagnosis, interquartile range for day of diagnosis, and middle 80% for day of diagnosis were determined. Timing was compared between uni-malleolar and bi-/tri-malleolar fractures. Results: The median day of diagnosis (and interquartile range; middle 80%) for myocardial infarction was 2 (1-5; 0-17), pneumonia 3 (2-7; 1-19), acute kidney injury 6.5 (2-18; 2-20), urinary tract infection 7 (2-14; 0-24), pulmonary embolism 10 (3-21; 0-27), sepsis 15 (4-22; 1-28), deep vein thrombosis 17 (10-22; 3-27), and surgical site infection 19 (14-25; 8-28; Figure 1). Myocardial infarction occured earlier in patients with bi-/tri-malleolar fractures than in patients with uni-malleolar fractures (median postoperative day 2 versus 10, p=0.041). Similarly, sepsis occured earlier in patients with bi-/tri-malleolar fractures than in patients with uni-malleolar fractures (median day 10 versus 20.5, p=0.022). For the other 6 adverse events, there was no difference in timing between patients with uni-malleolar and patients with bi-/tri-malleolar fractures (p>0.05 for each). Conclusion: These precisely described time periods for occurrence of specific adverse events enable heightened awareness amongst orthopaedic surgeons during the first month following open reduction and internal fixation of the ankle. Orthopaedic surgeons should have the lowest threshold for testing for each adverse event during the time period of greatest risk.